Disaster technology an annotated bibliography / by Diana H. Manning. - Manning, Diana H. (Diana Helen) (Pergamon Press, 1976)
Disaster Technology: An Annotated Bibliography presents an annotated bibliography of disaster technology. The references are arranged in the following sections: relief organization, medical aspects (planning, general, nutrition), sociological aspects, and physical aspects (general, earthquakes). The abstracts are arranged alphabetically by author's name in each section. Some of the controversial issues and the areas related to disaster technology are reviewed. This volume consists of seven chapters, the first of which introduces the reader to general aspects of relief work especially internati.
Keywords: Disasters -- Bibliography.; Disaster relief -- Bibliography.; Disaster relief.; Disasters.; Bibliographies.